Behavior of Ultra-High-Performance Concrete with Hybrid Synthetic Fiber Waste Exposed to Elevated Temperatures - Bassam Tayeh; Marijana Hadzima-Nyarko; Magdy Youssef Riad Riad; Radwa Defalla Abdel Hafez (Buildings, 2023)
The reinforcement of ultra-high-performance concrete (UHPC) with fibers was investigated in this study. Concrete is the most widely used manmade construction material, and UHPC has remarkable mechanical properties. The mechanical properties of UHPC can be modified by a variety of curing procedures and the amount of cement used. This study aimed to examine the impact of fiber reinforcement, temperature, and exposure time on UHPC. Initially, the temperature for UHPC was changed from 300 °C to 500 °C and the exposure time set to 1 and 2 h. Various combinations of the ultrasonic pulse, thermal conductivity, compressive strength, flexural strength, splitting, modulus of elasticity, and drop hammer impact (impact resistance, impact energy, and ductility index) were investigated after 91 days of steam curing. For steam curing, the temperature was kept at 90 °C for three days. The mechanical characteristics of UHPC were the primary focus of this research. The test results showed that the accelerated curing regime achieved a maximum compressive strength of 102.6 MPa for UHPC specimens without fibers and 124.7 MPa for UHPC specimens with fibers, which represents a 22% increase in compressive strength. When compared to UHPC without fibers, all the qualities of UHPC with fibers were improved, especially when subjected to high temperatures. The incorporation of hybrid synthetic waste fibers was a key aspect in developing new ultra-high-strength concrete features.